Infantile Crohn's disease is one of the risk factors for catheter‐related bloodstream infection. Issue 3 (June 2014) - Koike, Yuhki; Uchida, Keiichi; Inoue, Mikihiro; Ide, Shozo; Hashimoto, Kiyoshi; Matsushita, Kohei; Otake, Kohei; Ohkita, Yoshiki; Araki, Toshimitsu; Kobayashi, Minako; Mohri, Yasuhiko; Kusunoki, Masato
Abstract Background Central venous catheterization is recognized as a lifeline that is important for chemotherapy or nutritional support in pediatric patients with malignant disease and intestinal failure. This study analyzed the risk of infection with Broviac line use among these patients at a single Japanese center. Methods Two hundred and four Broviac lines were inserted in patients in the pediatric ward from January 2003 to October 2011. We analyzed the risk of catheter‐related bloodstream infection (CR‐BSI) using clinical characteristics including underlying disease, sepsis history, inserted situation, drug use, and laboratory data at the time of Broviac insertion or before CR‐BSI. Results During the study period, data from a total of 15 lines were excluded because of missing blood culture data. In the remaining 189 Broviac lines, 52 lines developed CR‐BSI. On univariate analysis, leukemia, infantile Crohn's disease, sepsis history before Broviac insertion, existence of a stoma opening, and immunosuppressant use before CR‐BSI were risk factors for CR‐BSI. On multivariate logistic regression analysis infantile Crohn's disease, sepsis history before Broviac insertion, and immunosuppressant use before CR‐BSI were independently associated with CR‐BSI (P = 0.015, P = 0.045, and P = 0.043, respectively). Conclusions Infantile Crohn's disease carries a high risk for CR‐BSI because of its pathological condition, the therapeutic drugs required, and surgical intervention.